Mental Maps as a Strategy in the Development of Successful Intelligence in High School Students - Núñez Lira, Luis Alberto (2019)
Mind maps are usually employed by teachers from all the educational levels as powerful learning strategies. This use enables important pedagogic achievements, but they do not exceed their maximum level, due to the dogmatic use of Tony Buzan's mind map (1996). Situation that would be different if it were entirely internalized, understand and applied. Precisely for that reason, the triarchic theory of intelligence developed by Rober Sternberg (1985) allows students to make decisions in several difficult situations with the suitable use of techniques and orientations in the development of the same intelligence. The research was developed by means of the case study from the qualitative focus, in which through the analysis of the evidences found and the use of an instrument that measured the successful intelligence, its development could be confirmed. However, the empiric analysis was not enough for validating the aforementioned development. For that reason, direct observation was chosen during learning sessions accomplished by the teacher responsible for the strategy to be used, and embodied in the field notebook. Likewise, in-depth interviews were conducted by educational psychologists. It should be noted that the analyzed documents have allowed developing the triangulation not only of evidences but also of methodologies, among them the documentary analysis, in order to reach conclusions that demonstrate how the development of the successful intelligence has been achieved. Finally, it is demonstrated than the use of the techniques of the mind maps with an educational strategy adapted to the applied group, achieves the significant development of the abilities of the analytical, creative and practical intelligence.